Bio-plasticizer production by hybrid acetone-butanol-ethanol fermentation with full cell catalysis of Candida sp. 99–125. (June 2018) - Chen, Changjing; Cai, Di; Qin, Peiyong; Chen, Biqiang; Wang, Zheng; Tan, Tianwei
Highlights: ABE fermentation was hybrid with full cell catalysis for butyl oleate production. ABE permeate after in situ pervaporation was applied for esterification. Wet Candida sp 99–125 cells were used as full-cell catalyst. 75% and 11.8% of butyl oleate and ethyl oleate were obtained after batch esterification. Abstract: Hybrid process that integrated fermentation, pervaporation and esterification was established aiming to improve the economic feasibility of the conventional acetone-butanol-ethanol (ABE) fermentation process. Candida sp 99–125 cells were used as full-cell catalyst. The feasibility of batch and fed-batch esterification using the ABE permeate of pervaporation (ranging from 286.9 g/L to 402.9 g/L) as substrate were compared. Valuable butyl oleate was produced along with ethyl oleate. For the batch esterification, due to severe inhibition of substrate to lipase, the yield of butyl oleate and ethyl oleate were only 24.9% and 3.3%, respectively. In contrast, 75% and 11.8% of butyl oleate and ethyl oleate were obtained, respectively, at the end of the fed-batch esterification. The novel integration process provides a promising strategy for in situ upgrading ABE products.